2014
DOI: 10.4049/jimmunol.1301656
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxvitamin D3 Promotes the Long-Term Effect of Specific Immunotherapy in a Murine Allergy Model

Abstract: Calcitriol (1α,25-dihydroxyvitamin D3) is the active vitamin D metabolite and mediates immunological functions, which are relevant in allergy. Its therapeutic use is limited by hypercalcaemic toxicity. We have previously shown that the activation of the vitamin D receptor inhibits IgE production and that B cells can synthesize calcitriol from its precursor 25-hydroxyvitamin D3 (inactive precursor) [25(OH)D] upon antigenic stimulation. In this study, we address the impact of 25(OH)D on the development of type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 45 publications
(59 reference statements)
0
33
0
3
Order By: Relevance
“…In Heine et al, vitamin D supplementation in vitamin D deficient mice resulted in immunomodulation, which favored protection against allergic triggers. Production of pro-inflammatory cytokines was reduced and that of anti-inflammatory cytokines was increased by vitamin D supplementation [22]. Jerzynska et al supplemented children with vitamin D during the pollen season and observed fewer manifestations of AR as compared to the placebo group [23].…”
Section: Discussionmentioning
confidence: 99%
“…In Heine et al, vitamin D supplementation in vitamin D deficient mice resulted in immunomodulation, which favored protection against allergic triggers. Production of pro-inflammatory cytokines was reduced and that of anti-inflammatory cytokines was increased by vitamin D supplementation [22]. Jerzynska et al supplemented children with vitamin D during the pollen season and observed fewer manifestations of AR as compared to the placebo group [23].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of VD3 (calcipotriol) may be ascribed to its ability to induce immune tolerogenic dendritic cells and Treg cells [25,26]. In addition, it also inhibits activated antigen-specific T cell response and IgE expression in B-cells [26,27]. CpG as an adjuvant showed potential benefit to alleviate allergy symptoms by inducing T H 1 response [7,15,23].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D has been shown to promote multiple types of regulatory T cell including those expressing FoxP3 and those secreting interleukin-(IL-) 10, as well as enhancing expression of other immunomodulatory molecules such as CD200 and CD73, whilst suppressing effector T cells such as those of Th17 subtype [11,12]. Consistent with this, Heine and colleagues have in mice shown vitamin D deficiency to increase specific Immunoglobulin E (IgE) responses in an allergen sensitization model, with vitamin D supplementation enhancing allergen immunotherapy [13].…”
mentioning
confidence: 86%